Comparison Of Android-Based Personal Financial Management Applications With Variative Financial Conditions - Liana Dewi (JAS (Jurnal Akuntansi Syariah), 2023)
Financial planning puts individuals in a better position to understand, manage and make financial decisions. Currently, there are various Android-based applications available to help manage personal finances. This study aims to make a comparison of Android-based personal financial management applications. Recording of 12 types of financial transactions is carried out using three financial management applications, namely Money Lover, Keuangan Pribadi Ku, and Catatan Keuangan Harian. Revenue, expenditure, and realization budget data have surplus, balanced, and deficit conditions prepared for input and processing in the three applications, with a comparison using ten parameters. The results of this study indicate that the three applications have standard features that can be used as tools in personal financial management. However, the Keuangan Pribadi Ku application does not provide features to handle recording when the financial condition is in a deficit and can only run well in balanced and surplus financial conditions. Meanwhile, the Money Lover dan Catatan Keuangan Harian provides features to record surplus, balanced, and deficit financial conditions. This research has contributed to increasing understanding and awareness of the importance of utilizing supporting technology in personal financial management and providing consideration for users in choosing a personal finance management application that suits their needs.